CONTEMPORARY ARTISTIC AQUILOMBAMENTOS:: SYMBOLIC RETERRITORIALIZATIONS IN BLACK BRAZILIAN PHOTOGRAPHY - Meirinho, Daniel (2022)
This paper investigates how the collective of Black photographers Afrotometria uses ancestral practices and social technologies of aquilombamento as a tactic of aesthetic contestation of the anti-racist representation regime. It outlines an overview of the strategic dimensions in a regime of visibility, representation, and modes of presence. It reflects on the relations established between authentic Black Brazilian quilombo based organization and resistance with the forms of artistic collectivity in the Afro-diasporic artistic presence. By means of interviews, this essay analyzes the possibility of new places of enunciation in contemporary Black Brazilian photography.